System for the visualization of food production indicators through the SAEN+C Pinar Observatory - Reinaldo Javier Rodríguez Font; Maidelyn Díaz Pérez; Pablo Ramón Brizuela Chirino (Cooperativismo y Desarrollo, 2022)
The country has different national programs that procure food. However, it is not possible to guarantee sufficient diversity in the food diet. The monthly subsidized food basket covers almost forty percent of the recommended energy intake, the rest is covered by households in non-subsidized markets characterized by irregular supply. This situation, in part, is generated by low productivity in the agro-industrial sector, low agricultural yields and high post-harvest losses, just to mention a few causes. Faced with this scenario, the country approved a plan to support, from science, food production as a way to achieve greater food sovereignty in the nation. This research aims to show the development of a system that allows the visualization of indicators related to food production in the territories, from the Observatory of Food Sovereignty and Nutritional Education of Pinar del Río. Theoretical and empirical methods were used, which allowed achieving a scientific, technological and practical result, considered relevant for the sector because it integrates in its various services analysis with indicators of different structure and analytical categories, measurement sources and technologies that facilitate the mapping of the baseline that each territory needs for its projection, planning and control of results. This system, in addition to working the baseline, is flexible and allows the introduction of new categories, analysis methodologies and indicators, which increase its prospective use value.